Educação sexual nos anos iniciais do ensino fundamental : concepções e práticas. - Santos, Claudete Martins (2011)
Sex education addresses issues related to the sexuality such as: their manifestations, gender issues, the respect for sexual diversity, the construction of the concept of masculinity and femininity, the body care etc. We understand that children bring to school issues related to sexuality, for example, questions regarding their origin and discovery of sexual pleasure. For a long time, the practice of sex education was a scene of fights between the sex educators and society/church/politics. In our history, this practice was, at times, repressive and, in others, was suppressed. Their legitimacy, in Brazil, occurred after the implementation of the National Curriculum Parameters, however it is noted that their inclusion in the curriculum has not been satisfactorily yet. From this context, this research investigates how sexuality is being worked (or not) by the teachers of early years of elementary school of Municipal Schools of Aracaju. For this, we used a qualitative methodology based on the following instruments to collect data: questionnaire and interview with teachers from 1st to 5th year of ten schools. The purpose of data collect was determine if teachers work the topic of sexuality in the classroom and, if they have, we seek to identify the work methodology and the difficulties faced. In case of negative responses, we investigate the reasons for them and what is the opinion about the contribution of sex education for child development. It was found that the teachers surveyed recognize the importance of discussing this issue with their students. These teachers have a medical biologizing conception of sexuality and sex education. Although most of these teachers assert that this issue is addressed in classroom, they face difficulties related to their own unpreparedness and also to the prejudice of fathers and mothers, as well as students, especially. Most informants believe that the matter is more easily approached when a woman (teacher) is ahead, because she represents a mother figure, the caregiver children. Sex education is seen by teachers as a means of preventing disease and pregnancy; therefore, they consider necessary a training program focused in this educational practice, this program should be promoted by public managers. Starting from the idea that sexuality is a human dimension that goes beyond the anatomo-biological-reproductive condition, this work indicates the emergence of discussions about the issue in the educational circles, this discussions based in emancipator approach.